BENTUK PENYAJIAN TARI SELODANG MAYANG DI KERATON KESULTANAN KADRIYAH PONTIANAK KALIMANTAN BARAT - Nurul Oky Azmadanty; Ismunandar Ismunandar; Regaria Tindarika (Universitas Tanjungpura, 2021)
AbstractThe background of this research is to describe the form of presentation of Selodang Mayang Dance. Selodang Mayang dance is a classical dance which is a specifically performed at the Kadriyah Sultanate Palace and there is very little information about classical dance in West Kalimantan. This study aims to describe and document the Selodang Mayang dance in the form of writing, pictures and videos of the dance. The problem in this research is: how is the the Selodang Mayang dance at the Kadriyah Sultanate Palace has been presented. This is a qualitative research method through the descriptive approach and this used Seodarsono theory assisted by ethnochoreology approach, with source of data wasin the form of Selodang Mayang Dance. The resource of this study were Syarifah Fadlon Alkadrie, Syarifah Faizah Alkadrie, and Riana Utami. Data collection techniques were observation, interviews, and documentation. The validation techniques of the data used were the extension of observations and triangulation. Based on the results of the researchers, it is concluded that the form of presentation of the Selodang Mayang dance at the Kadriyah Sultanate Palace, Pontianak, West Kalimantan, are as follows: The name of the Selodang Mayang dance was taken from the names of the shawl and mayang or areca nut. Selodang Mayang dance is a group dance. Selodang Mayang dance moves consist of opening movements, core movements, namely varieties 1, 2, and 3 and closing movements. Musical instruments that can be used to accompany this dance are the tambourine and the accordion. Selodang Mayang dance is using realist makeup. The clothes worn by dancers are telo 'potass clothes and gill pattern cloth. The properties used are shawl and mayang or areca nut.Keywords: Dance, Selodang Mayang, Presentation